PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MATERI KONSEP DASAR PECAHAN MADRASAH IBTIDAIYAH BERVISI SETS DI MI AL HADI GIRIKUSUMA - Linda Indiyarti Putri (LP2M, 2017)
Experience is the result of the construction of interaction with the environment. Learningsimple fractional concepts can be learned through connecting with everyday experiences.Simple fractional linkages with SETS (Science, Technology, Environment and Society) can helpbuild cognitive structures and build creativity in learners. This study aims to obtain productdevelopment of learning tools of mathematics with vision of SETS to improve learners'learning outcomes, as well as to know the validity, reliability and effectiveness of developeddevices. The research was conducted at MI Al Hadi Girikusuma Mranggen Demak by using4-D model (define, design, develope and desseminate) from Thiagarajan, Semmel and Semmel.Research conducted is research and development (R and D). The development of this learningtool can improve students' learning in the cognitive domain. Percentage mastery reached87.5% as many as 35 students and learning outcomes increased significantly.Keywords: learning tool, basic concept of fractional, SETS Experience